Scientometric analysis of Mycobacterium tuberculosis revaccination: Dynamics, impact and analysis of collaborative networks - Luis Roberto Checa Vieira; Aylén Solange Vásquez Dávila; Frank Mayta-Tovalino (Lung India)
Background: Mycobacterium tuberculosis (M. tuberculosis) is an infectious disease that remains a significant global health problem. Despite efforts to reduce the disease, the disease remains prevalent in many parts of the world. This study aims to analyse the dynamics, impact and analysis of collaborative networks in revaccination against M. tuberculosis through a scientometric study in Scopus (2018–2024). Methods: This study is retrospective, descriptive and observational, and everything was carried out with a scientometric approach in which the unit of analysis was all publications in journals indexed in the Scopus database between 2018 and 2024, without language limitation. To collect the articles, an advanced search strategy was carried out in the Scopus database. Specific search criteria were defined using combinations of key terms such as ‘revaccination’ and ‘M. tuberculosis’, articulated through Boolean operators to optimize the relevance of the results. Results: The most productive institution was the University of Cape Town, while University College London had the highest citation impact. Frontiers in Immunology was the most productive journal, with Nature Communications having the highest citation count. The Hatherill Mark was the most prolific author with 17 publications, although the highest h-indexes did not necessarily correspond to the most productive authors. An increase in the number of publications was observed, peaking in 2020 at 52 publications. In terms of collaboration, strong networks were identified between countries such as the United States, the United Kingdom and China, with authors such as Hatherill Mark and Scriba Thomas J. occupying central positions in these networks. Conclusions: This scientometric analysis highlights the growing interest in tuberculosis revaccination, with an increase in scientific production and international collaboration. However, the variability in the quality of publications emphasizes the need to promote high-quality research and innovative strategies to improve global health.